Belting : a guide to healthy, powerful singing - GagnÃ©, Jeannie Wolff (Berklee Press, 2015)
'Belting' picks up where the author's first book, 'Your singing voice' left off. It teaches how to sing loud, powerful vocals that won't hurt, crack, sound bad, or stop your vocal chords from functioning properly.